Pseudodifferential Operators with Automorphic Symbols - Unterberger, André (Pseudo-Differential Operators, Theory and Applications, 2015)
The main results of this book combine pseudodifferential analysis with modular form and L-function theory, with the help of explicit spectral-theoretic calculations. The starting point is a notion of modular distribution in the plane, which will be new to most readers and which, under the Radon transformation, relates to the classical notion of non-holomorphic modular form. Holomorphic modular forms are also briefly considered, within a general scheme that addresses quantization theory and elementary but novel representation-theoretic concepts.